A Study of Bipolar Fuzzy Soft Sets and Its Application in Decision-Making Problems. (19th October 2021) - Mustafa, Saima; Safdar, Neelofar; Bibi, Murrium; Sayed, A.F.; Khan, Muhammad Ghaffar; Salleh, Zabidin
Abstract : We live in a society where we have to deal with so many social issues daily, and making a right choice is everyone's main concern. This study is based on the selection of right university while getting admission which is the core issue for students nowadays. We are concerned with bipolar fuzzy multicriteria decision-making methods. The main purpose is to provide guidance to the students for determining the best university and evaluating the factors that are affecting while getting admission. We thus combined bipolar fuzzy and soft expert sets to give multicriteria decision-making approach that overcomes the issues that arise while taking decisions. This study involves the development of structural hierarchical models of parameters and the implementation of soft expert sets to make the decision-making problem much more precise by introducing a new algorithm. Thus, this model is helpful for multicriteria decision making and can be used for university selection and thus suitable for education sector as well.